2021
DOI: 10.3390/coatings11080970
|View full text |Cite
|
Sign up to set email alerts
|

The Local Distribution of Temperatures and Entropy Generation Rate in an Ideal Counterflow Heat Exchanger

Abstract: The process of heat exchange between two fluids of different temperatures and separated by a solid wall occurs in many engineering applications. Log mean temperature difference and effectiveness-NTU methods are widely used to assist in the design of heat exchangers. However, the two methods focus on overall analysis and cannot show the local temperature distributions. This paper obtains the mathematical solutions to the temperature profiles in an ideal counterflow heat exchanger. The aim of this research is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previously, it has been extensively used for analysis of thermofluid systems. [31][32][33][34][35][36][37][38][39][40][41] In a recent study by Charoen-amornkitt et al 18 the authors used NET to describe entropy generation in a chemical reactor. The entropy production approach based on NET of physical processes at the interfaces has been applied for efficiency improvement in PEM fuel cells with porous electrodes.…”
Section: A Oxmentioning
confidence: 99%
“…Previously, it has been extensively used for analysis of thermofluid systems. [31][32][33][34][35][36][37][38][39][40][41] In a recent study by Charoen-amornkitt et al 18 the authors used NET to describe entropy generation in a chemical reactor. The entropy production approach based on NET of physical processes at the interfaces has been applied for efficiency improvement in PEM fuel cells with porous electrodes.…”
Section: A Oxmentioning
confidence: 99%
“…Furthermore, they added that compared to pure HFE7000 flowing in a no-slip pipe with a slip length of 100 m and a 6% volume concentration of Al 2 O 3 dispersed in HFE7000, total entropy generation was reduced by about 20% when using a slipping wall pipe with a slip length of 100 m and a 6% volume concentration of Al 2 O 3 . Other important studies on entropy generation can be found in the literature [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%